2021
DOI: 10.17049/ataunihem.500301
|View full text |Cite
|
Sign up to set email alerts
|

Geleneksel Ve Tamamlayici Tip Uygulamalarinin Gülen Yüzü: Kahkaha Yogasi

Abstract: Genellikle kahkaha, mutluluğun görsel bir şekilde anlatımı ya da sevinç duygusu olarak kabul edilmektedir. Gülmenin insan vücudunu fizyolojik ve psikolojik olarak olumlu yönde etkilediği bilinmektedir. Kahkaha yogasını, gevşeme ve nefes egzersizlerinin birleşmesinden oluşan nefes teknikleri ve koşulsuz kahkahadan oluşan egzersizler oluşmaktadır. Kahkaha yogası farklı hastalıklara (kanser, diyabetes mellitus vb) bağlı ortaya çıkan semptomların şiddetinin azaltılmasında ve mevcut durumun (stres) iyileştirilmesin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
1
4
0
1
Order By: Relevance
“…In their study in which breast cancer patients participated in four sessions of laughter yoga practice, Kim et al [21] reported that laughter yoga practice signifcantly reduced anxiety and depression levels in the intervention group but did not cause any change in the control group. Te analysis of the physiological process of laughter yoga practice in the body revealed that laughing increased the release of endorphins, reduced stress, and led to mental and physical relaxation [14]. Tis result suggests that laughter yoga practice can be interpreted as one of the methods that help the person manage stress indicated in the stay optimistic behaviors and problem solving behaviors subdimensions.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In their study in which breast cancer patients participated in four sessions of laughter yoga practice, Kim et al [21] reported that laughter yoga practice signifcantly reduced anxiety and depression levels in the intervention group but did not cause any change in the control group. Te analysis of the physiological process of laughter yoga practice in the body revealed that laughing increased the release of endorphins, reduced stress, and led to mental and physical relaxation [14]. Tis result suggests that laughter yoga practice can be interpreted as one of the methods that help the person manage stress indicated in the stay optimistic behaviors and problem solving behaviors subdimensions.…”
Section: Discussionmentioning
confidence: 95%
“…Laughter yoga is a nonpharmacological practice including a series of exercises that combine laughter for no reason with yoga and breathing techniques that can be performed by students on their own in daily life. As emphasized in several studies, laughter yoga creates a good mood in people, contributes to the creation of a happy environment, and improves their adaptation to their environment [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bu çalışma, hasta ve ailesine 24 saat bakım verme görevi olan (Özer & Ateş, 2021), hem tıbbın kabullerini taşıyan hem de hasta ve yakınlarıyla birebir ilişki kurarak tıp ve toplum arasında köprü konumundaki hemşirelerin ötanaziyi, ölümü ve ölümcül hastayı nasıl tanımladığı ve deneyimlerinin neler olduğunun anlamlandırılmasını…”
unclassified